Rancang Bangun Sistem Monitoring Lingkungan Pada Kandang Sapi Berbasis Internet of Things - Untoro, Fendi; Nurchim, Nurchim; Pramono, Pramono (LPPM STIKI MALANG, 2025)
Cows are livestock that are generally kept by the community, especially in rural areas. According to data from the Central Statistics Agency (BPS), in 2021 the beef cattle population reached 17,977,214, an increase compared to the previous year which was recorded at 17,440,393. Environmental factors in cow sheds can directly affect livestock, causing stress due to extreme temperatures, both hot and cold, resulting in decreased feed consumption and discomfort. High levels of ammonia gas from cow dung waste can affect cow resistance to disease and reduce cow productivity and can cause health problems for the surrounding community. This study aims to design an Internet of Things (IoT)-based cow shed environmental monitoring system. The method in this study uses several stages, namely data collection, needs analysis, design, planning and testing. The system created can monitor temperature, humidity and ammonia gas in the cow shed environment and display this information on a mobile application. In the mobile application, information from sensor values ​​can be displayed in high, medium, and low categories during monitoring. The tool testing technique was carried out with 10 samples, the results showed that the temperature detector had an accuracy level of 91.13%, the humidity detector showed a value of 94.52% and the ammonia gas detector showed the highest value of 34.8 ppm at a distance of 10 cm and the smallest of 6.6 ppm at a distance of 100 cm. The results of this study indicate that the developed IoT system is effective in monitoring important parameters such as temperature, humidity, and ammonia gas in real-time. This can increase efficiency for farmers in monitoring environmental conditions in the cage, which was previously done manually.